1975
DOI: 10.1002/aja.1001440304
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of normal rat liver: The surface structure of its cells and tissue components

Abstract: Scanning electron microscopy (SEM) allows the surface ultrastructure of intrahepatic cells and other tissue components of liver to be delineated. Excellent depth of focus of the SEM makes it possible to visualize surfaces of intact cells in their native configurations. This report details the surface characteristics and inter-relationships of hepatocytes and hepatic plates, sinusoidal endothelial cells and sinusoids, presumed Kupffer cells, vessels, bile ducts, connective tissue, and the capsule of rat liver. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 16 publications
2
32
2
Order By: Relevance
“…The fenestration sizes documented here for each zone correspond well with several published reports on rat liver SEC, indicating that zone 1 (we report 76.57 nm) fenestrations are smaller than those in zone 3 (we report 97.92 nm), 23,24 but others describe the opposite. 9,26,27 The reasons for these discrepancies are unclear, but strain, age and weight of rat, metabolic differences among the animals used, preparation of tissue, as well as sampling techniques in these studies may contribute to variation in mean fenestration size. Inclusion of "gaps"-those pores larger than 300 m in diameter-as fenestrae could skew the mean diameter to the larger size, especially if there are more "gaps" in zone 1 than zone 3.…”
Section: Discussionmentioning
confidence: 99%
“…The fenestration sizes documented here for each zone correspond well with several published reports on rat liver SEC, indicating that zone 1 (we report 76.57 nm) fenestrations are smaller than those in zone 3 (we report 97.92 nm), 23,24 but others describe the opposite. 9,26,27 The reasons for these discrepancies are unclear, but strain, age and weight of rat, metabolic differences among the animals used, preparation of tissue, as well as sampling techniques in these studies may contribute to variation in mean fenestration size. Inclusion of "gaps"-those pores larger than 300 m in diameter-as fenestrae could skew the mean diameter to the larger size, especially if there are more "gaps" in zone 1 than zone 3.…”
Section: Discussionmentioning
confidence: 99%
“…MOTTA andFUMAGALLI (1974) andGRISHAM et al (1975) demonstrated, in biliary ductular lumina of normal rat livers, single cilia as were curved and twisted at many points, sometimes crossing the ductal lumen. BROOKS et al (1975) also observed cable-like structures, some of which they identified as cilia by transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that ciliated cells may occur in normal intrahepatic bile ductal epithelium was produced with the transmission and scanning electron microscope by GRISHAM (1963), STERNLIEB (1965), MOTTA andFUMAGALLI (1974) andGRISHAM et al (1975) in normal human and rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…During these last two decades, scanning electron microscopic (SEM) techniques have greatly contributed towards the visualization of the three-dimensional microstructure of the liver (FUJITA, TOKUNAGA and INOUE, 1971;ITOSHIMA et al, 1974;GRISHAM et al, 1975;LAYDEN et al, 1975;MUTo, 1975;MUTO et al, 1977;MOTTA and PORTER, 1974;MOTTA, 1975MOTTA, , 1977MOTTA, , 1978MOTTA, , 1984MOTTA, MUTO and FUJITA, 1978;KESSEL and KARDON, 1979;VONNAHME, 1981, TAKAHASHI-IWANAGA andFUJITA, 1986). However, the threedimensional organization of the collagen fibrils has *This investigation was supported by a grant from the Ministry of Education, Science and Culture, Japan (63570009).…”
Section: Discussionmentioning
confidence: 99%